2020
DOI: 10.1007/s00261-020-02747-5
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal CT in COVID-19 patients: incidence, indications, and findings

Abstract: Purpose The purpose of this study was to evaluate the frequency, indications, and findings of abdominal CTs ordered in the initial evaluation of patients who had a positive COVID-19 test performed in our institution. Methods Retrospective chart review was performed on all patients who had a positive test for COVID-19 performed at a single quaternary care center from 1/20/2020 through 5/8/2020. In a subset of patients undergoing abdominal CT as part of the initial evaluation, the demographics, suspected COVID-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 17 publications
(36 reference statements)
4
15
0
Order By: Relevance
“…Similar to the GI findings, the overall incidence of abdominal findings especially biliary or gallbladder findings were also low in incidence in our study compared to other studies [ 12 14 , 18 ]. This is similar to the observation of Barkmeier et al who found that 63% of patients with abdominal symptoms and COVID-19 had negative CT scans [ 10 ]. The incidence of gallbladder sludge was 2/24 patients with abdominal CT and 1/4 patients with ultrasound.…”
Section: Discussionsupporting
confidence: 91%
“…Similar to the GI findings, the overall incidence of abdominal findings especially biliary or gallbladder findings were also low in incidence in our study compared to other studies [ 12 14 , 18 ]. This is similar to the observation of Barkmeier et al who found that 63% of patients with abdominal symptoms and COVID-19 had negative CT scans [ 10 ]. The incidence of gallbladder sludge was 2/24 patients with abdominal CT and 1/4 patients with ultrasound.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, in their study, Barkmeier et al stated that there were 42 patients with COVID-19 have abdominal CT that visualized lung bases. They also stated that 79% of these patients have abnormal CT findings on lung bases (13). In this present study, we found that 9.7% of the patients had abnormal CT findings consistent with COVID-19 pneumonia.…”
Section: Discussionsupporting
confidence: 66%
“…The patients who are not yet suspected COVID-19 may have been characteristic pulmonary findings of COVID-19 pneumonia. Also, CT findings are could be support COVID-19 in patients who are investigated to novel viral pneumonia infection (13). The commonly characteristic CT patterns for COVID are included in; ground-glass opacities, bilateral or multilobar involvement, cavitation, bilateral patchy shadowing, septal or pleural thickening, linear opacities, and discrete pulmonary nodules etc.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 1057 patients with COVID-19 and GI complaints, abdominal CTs were warranted in just 4%, the majority of which (63%) showed no acute abnormality[ 120 ]. Bowel wall abnormalities have been observed in 3% of hospitalized patients with COVID-19[ 122 ].…”
Section: Extrapulmonary Manifestationsmentioning
confidence: 99%